2019
DOI: 10.1136/archdischild-2018-316519
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of functional neurological disorder in children

Abstract: ObjectivesTo establish the incidence and long-term outcomes (up to 21 years) of children presenting to a University hospital paediatric neurology service with symptoms due to functional neurological disorder (FND) with particular reference to occurrence of FND or similar symptoms in adulthood.MethodsRetrospective chart review to determine characteristics of the original paediatric FND presentation plus record-linkage with providers of Child and Adolescent Mental Health Services. Chart review of adult medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
4
20
1
Order By: Relevance
“…Research suggests children with FND have a 77% rate of remission in adulthood [3] . However, duration of symptoms is associated with prognosis [8] , [9] , and prolonged symptoms of FS during childhood likely have negative long-term psychosocial effects [25] , making prompt resolution of FS critical to children’s long-term wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests children with FND have a 77% rate of remission in adulthood [3] . However, duration of symptoms is associated with prognosis [8] , [9] , and prolonged symptoms of FS during childhood likely have negative long-term psychosocial effects [25] , making prompt resolution of FS critical to children’s long-term wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Functional seizures (FS; also known as psychogenic nonepileptic seizures or PNES) are a type of functional neurological disorder (FND) in which patients experience seizure-like symptoms that are not associated with epileptiform activity [1] . About one in five patients in seizure clinics are diagnosed with FS [2] , and in children under 16, the incidence of FND in pediatric neurological services is at least 6 per 100,000x [3] .…”
Section: Introductionmentioning
confidence: 99%
“…When unrecognized and untreated, SSD could be extraordinarily disabling and might lead to a progressive loss of life and social opportunities for intellectual growth. It may result in a poor adulthood outcome, leading to a permanent functional disability (20,21). Therefore, the ED setting can represent a unique window of opportunity to identify and support these patients.…”
Section: Recommended Management In the Edmentioning
confidence: 99%
“…Though published studies have revealed the importance of recognising and treating functional symptoms in adults, the literature in children is sparse. Raper and colleagues in this issue add significantly to our knowledge by reporting on a 20-year experience, in their centre, of children with functional neurological disorder (FND) 1. FND, also known as conversion disorder, refers to a spectrum of neurological symptoms which have no established neurological cause and are assumed psychological in origin.…”
Section: The Size Of the Problem?mentioning
confidence: 99%